Optimizing the Performance of CsPbI3-Based Perovskite Solar Cells via Doping a ZnO Electron Transport Layer Coupled with Interface Engineering - Yue, Man; Su, Jie; Zhao, Peng; Lin, Zhenhua; Zhang, Jincheng; Chang, Jingjing; Hao, Yue (Nano-Micro Letters, 2019)
Interface engineering has been regarded as an effective and noninvasive means to optimize the performance of perovskite solar cells (PSCs). Here, doping engineering of a ZnO electron transport layer (ETL) and CsPbI3/ZnO interface engineering via introduction of an interfacial layer are employed to improve the performances of CsPbI3-based PSCs. The results show that when introducing a TiO2 buffer layer while increasing the ZnO layer doping concentration, the open-circuit voltage, power conversion efficiency, and fill factor of the CsPbI3-based PSCs can be improved to 1.31 V, 21.06%, and 74.07%, respectively, which are superior to those of PSCs only modified by the TiO2 buffer layer or high-concentration doping of ZnO layer. On the one hand, the buffer layer relieves the band bending and structural disorder of CsPbI3. On the other hand, the increased doping concentration of the ZnO layer improves the conductivity of the TiO2/ZnO bilayer ETL because of the strong interaction between the TiO2 and ZnO layers. However, such phenomena are not observed for those of a PCBM/ZnO bilayer ETL because of the weak interlayer interaction of the PCBM/ZnO interface. These results provide a comprehensive understanding of the CsPbI3/ZnO interface and suggest a guideline to design high-performance PSCs. Highlights: 1 Device simulations and first-principle calculations are employed to derive a guideline for the optimization of CsPbI3-based perovskite solar cells (PSCs). 2 The open voltage and power conversion efficiency of the PSCs are, respectively, improved to 1.31 V and 21.06% by simultaneously introducing an ultra-thin TiO2 buffer layer and increasing the doping concentration of the ZnO electron transport layer. 3 The influence of the interfacial buffer layer and doping of the CsPbI3/ZnO interface on PSC performance is discussed.